2021
DOI: 10.1109/tpel.2020.3045596
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Electric Motor Temperatures With Deep Residual Machine Learning

Abstract: Most traction drive applications lack accurate temperature monitoring capabilities, ensuring safe operation through expensive oversized motor designs. Classic thermal modeling requires expertise in model parameter choice, which is affected by motor geometry, cooling dynamics, and hot spot definition. Moreover, their major advantage over data-driven approaches, which is physical interpretability, tends to deteriorate as soon as their degrees of freedom are curtailed in order to meet the real-time requirement. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(46 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…Consequently, surrogate models based on parametric or semi-parametric approaches might not follow accurate results in general. Through several attempts on machine learning methods, it is found that deep learning algorithms, like CNN and RNN, are good at the distribution estimation of magnetic field and temperature [129][130][131], and the prediction of torque and efficiency for motors [132][133][134]. These works established a solid foundation for the generalizable data-driven model for the analysis, design, and optimization of electromagnetic devices [129].…”
Section: Machine Learning For Performance Prediction Of Electromagnetmentioning
confidence: 99%
“…Consequently, surrogate models based on parametric or semi-parametric approaches might not follow accurate results in general. Through several attempts on machine learning methods, it is found that deep learning algorithms, like CNN and RNN, are good at the distribution estimation of magnetic field and temperature [129][130][131], and the prediction of torque and efficiency for motors [132][133][134]. These works established a solid foundation for the generalizable data-driven model for the analysis, design, and optimization of electromagnetic devices [129].…”
Section: Machine Learning For Performance Prediction Of Electromagnetmentioning
confidence: 99%
“…This testing step analyzes how well the found model generalizes to unseen data, which were not part of the training set. [106]): X denotes model inputs, i.e., measured quantities which are basically available in the motor control unit while Y represents the temperature targets to be estimated. For the data acquisition process, special motors with additional temperature sensors are required.…”
Section: Training and Testing Pipelinesmentioning
confidence: 99%
“…Typical examples are recurrent networks with internal memory cells or convolutional neural networks with large time spans of past data at their input (cf. [106], [115]). Recently, state-space neural networks with a special recurrent structure mimicking state-space model dynamics have been also introduced [118].…”
Section: Available Publications and Interim Conclusionmentioning
confidence: 99%
“…[89] relies on the high-frequency inductance for temperature estimation. References [90][91][92] belong to the AI-based methods. [93][94][95][96][97][98][99] are literatures about the characteristics of PM materials.…”
Section: Research Trend For Extensive Monitoring For Pm Machinesmentioning
confidence: 99%